DETERMINANTS OF PURCHASE DECISIONS JANJI JIWA COFFEE BALIKPAPAN WITH CONSUMER TRUST AS THE INTERVENING VARIABLE - Hasan, Syahril; Fitriana, Fitriana; Faizal, Muhammad (Universitas Muhammadiyah Kalimantan Timur, 2022)
This study aims to know and explain the factors that influence the variable purchasing decisions namely brand image and to see the influence of consumer confidence variables as intervening variables directly and indirectly to the purchase decision of Kopi Janji Jiwa Balikpapan jilid 630. Population in this study is consumers of Kopi Janji Jiwa Balikpapan Jilid 630 who bought in March 2021, which amounted to 9,305 customers and sampled as many as 100 people because of the large number of populations using slovin formula. The method of data collection uses questionnaires that are shared directly with respondents. Data analysis used is path analysis and sobel test as well as classic assumption test and for data processing using SPSS version 25, the data analysis method was carried out with multiple linear regression models and hypothesis testing use part analysis. The results showed that: 1. variable brand image to purchasing decisions have a positive and significant influence on purchasing decisions. 2. variable brand image to consumer confidence has a positive and significant influence on purchasing decisions. 3. Variable consumer confidence in purchasing decisions has a positive and significant influence on purchasing decisions. 4. the influence of brand image variables on purchasing decisions through consumer confidence variables as intervening variables has a positive and significant influence. The influence of brand image on purchasing decisions indirectly is greater in value compared to the direct influence which can be said to have a significant positive effect on purchasing decisions.